Ferroelectric and Optoelectronic Coupling Effects in Layered Ferroelectric Semiconductor‐Based FETs for Visual Simulation - Can Zhao; Zhaotan Gao; Zian Hong; Hongzhi Guo; Zhili Cheng; Yawei Li; Liyan Shang; Liangqing Zhu; Jinzhong Zhang; Zhigao Hu (Advanced Science)
Abstract Controlling polarization states of ferroelectrics can enrich optoelectronic properties and functions, offering a new avenue for designing advanced electronic and optoelectronic devices. Here, ferroelectric semiconductor‐based field‐effect transistors (FeSFETs) are fabricated, where the channel is a ferroelectric semiconductor (e.g., α‐In2Se3). Multiple conductance states are achieved in α‐In2Se3‐based FeSFETs by controlling the ferroelectric polarization. The on/off current ratio (Ion/Ioff) is ≈105 with a dark current of ≈10−11 A by applying a single positive gate voltage pulse. Moreover, the device shows excellent endurance and retention performance. In a further step, the carrier transports and corresponding physics mechanism in various polarization states are studied by using Kelvin probe force microscopy (KPFM) and optoelectronic measurements. Finally, the α‐In2Se3‐based FETs can be trained. It can recognize handwritten digit images from MNIST dataset with a successful recognition accuracy of ≈95.5%. This work provides a new design idea and theoretical support for advanced optoelectronic devices in the field of in‐memory sensing and computing.